Synthesis of a Cu2O/Carbon Film/NiCoB‐Graphene Oxide Heterostructure as Photocathode for Photoelectrochemical Water Splitting. Issue 7 (22nd February 2019) - Yu, Chunlin; Zhang, Xingwang
Abstract: Photoelectrochemical cells (PECs) for water splitting offer a promising way to convert solar energy into chemical energy. The electron transfer rate and surface‐catalyzed ability toward the hydrogen evolution reaction (HER) play key roles in the efficiency of PEC water splitting. In this work, a photocathode based on a Cu2 O/Carbon film/NiCoB‐graphene oxide (Cu2 O/C/NiCoB−GO) heterostructure is fabricated. The thickness‐controllable carbon film served as the electron transport and protective layer with favorable optical properties. The NiCoB‐GO amorphous catalyst displays efficient performance towards HER in neutral condition. The optimized photocathode shows a PEC‐HER performance with a photocurrent density of −2.9 mA/cm 2 at 0 V vs. RHE, and it also presents better stability than bare Cu2 O. This work provides a novel heterostructure photocathode for promoting solar‐driven PEC water splitting efficiently. Abstract : Let there be light : a hybrid Cu2 O/carbon film‐NiCoB‐graphene oxide photo cathode for photoelectrochemical water splitting is prepared. Benefiting from the thickness controllable carbon film with excellent conductivity and the amorphous NiCoB‐GO catalyst with a high number of exposed active sites, photo‐induced electrons can efficiently be extracted and utilized to achieve an improved photocurrent density of −2.9 mA⋅cm −2 at 0 V vs. RHE under illumination with visible light (100 mW/cm 2, AM 1.5 filter).